The political economy of tobacco of Zimbabwe: An analysis of stakeholder perspectives. - Shashika Bandara; Artwell Kadungure; Nhamo Nhamo; Tendai Nyashanu; Ashley Chamunorwa; Jeffrey Drope; Matthew Hunt; Alayne Adams; Raphael Lencucha (PLOS Global Public Health, 2025)
Tobacco continues to be viewed as a path to economic development by some governments, including Zimbabwe, despite widespread knowledge of tobacco's negative consequences for users, farmers and the environment. Zimbabwe is one of the top five tobacco producers in the world and the largest tobacco producer in the African region. Zimbabwe's focus on tobacco production creates difficulties for the implementation of the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) which it signed in 2014. Our objective was to understand the political economy of tobacco in Zimbabwe, which can inform the implementation of WHO FCTC. We conducted 23 interviews with government, non-governmental, para-statal and other stakeholders in Zimbabwe's tobacco sector. The findings illustrate intersecting issues that make tobacco a complex policy issue in the country. Interviewees indicated that WHO FCTC implementation faces barriers due to tobacco being an important economic commodity. Specifically, interviewees highlighted the prioritization of tobacco in government strategic plans and as a priority agricultural crop. Additionally, lack of alternatives and debt obligations makes it challenging for smallholder farmers to shift away from tobacco. However, findings indicate that tobacco production is facing rising challenges including tobacco use among youth, deforestation and farmer health, poverty and debt making the supply and demand measures of the WHO FCTC even more crucial. These challenges may be starting points to engage with the government in order to encourage strategies to move away from tobacco as a key economic commodity.